Two Neuter Pronouns in Picard - Auger, Julie (Arborescences)

(untitled) (Département d'études françaises, Université de Toronto, 2020)
In the Vimeu variety of Picard, a Gallo-Romance closely related to French, three different neuter subject clitic pronouns are found: a, ch’, and a null form. This paper examines the distribution of these forms in contemporary texts in order to determine the extent to which these pronouns resemble those found in other Gallo-Romance languages or whether their source must be sought in colloquial varieties of French. We argue, based on phonological, syntactic, and semantic criteria, that the French origin better accounts for the similarities between the two varieties. Based on their syntactic distribution, we argue that the three forms represent two different pronouns, a and ch’, that the null form is an allomorph of a in certain phonological contexts, and that the distinction between a/Ø and ch’ constitutes an innovation in Picard.